Recent advances of tanshinone in regulating autophagy for medicinal research - Wu, Sha; Zhao, Kui; Wang, Jie; Liu, Nannan; Nie, Kaidi; Qi, Luming; Xia, Lina (Frontiers in Pharmacology, 2023)
Initially described as an ancient and highly conserved catabolic biofunction, autophagy plays a significant role in disease pathogenesis and progression. As the bioactive ingredient of Salvia miltiorrhiza, tanshinone has recently shown profound effects in alleviating and treating various diseases by regulating autophagy. However, compared to the remarkable achievements in the known pharmacological effects of this traditional Chinese medicine, there is a lack of a concise and comprehensive review deciphering the mechanism by which tanshinone regulates autophagy for medicinal research. In this context, we concisely review the advances of tanshinone in regulating autophagy for medicinal research, including human cancer, the nervous system, and cardiovascular diseases. The pharmacological effects of tanshinone targeting autophagy involve the regulation of autophagy-related proteins, such as Beclin-1, LC3-II, P62, ULK1, Bax, ATG3, ATG5, ATG7, ATG9, and ATG12; the regulation of the PI3K/Akt/mTOR, MEK/ERK/mTOR, Beclin-1-related, and AMPK-related signaling pathways; the accumulation of reactive oxygen species (ROS); and the activation of AMPK. Notably, we found that tanshinone played a dual role in human cancers in an autophagic manner, which may provide a new avenue for potential clinical application. In brief, these findings on autophagic tanshinone and its derivatives provide a new clue for expediting medicinal research related to tanshinone compounds and autophagy.